(untitled) (Conference Zone, 2022)
In the development of the design competency of future drawing science teachers through the AutoCAD graphics program, the activity in the organization and conduct of training sessions, the intensity in the performance of the teaching task, as well as the implementation of independence require the need to rely on several didactic and methodological foundations. This didactic-methodical basis was the following: To develop the technology of developing the design competency of future drawing science teachers through the AutoCAD graphics program